PENGOLAHAN LJMBAH HASIL PERTANIAN DENGAN POKOK PERHATIAN KEPADA LIMBAH KELAPA SAWIT - R Sudradjat; Dedi Hartadi (Jurnal Penelitian Hasil Hutan, 1992)
The experivnent  deals with conversion   of oil palm shell lo  activated carbon, solid state fermentation of oil palm wastes i.e :  empty fruit  bunch  (EFB). pericarp  as   well as King grass,   bagasse, sago waste and cayepus leaves residue.  The experiment  was conducted  also on  liquid  state fennentation   of oil palm  process   water i. e : waste waler coming from fresh fruit  bunch  (FFB)  sterilization part and mud  waste from oil extraction part.  The method used for solid and liquid  state fermentation were  set at  about   optimum condition process  according to the previous  experiments.The results showed tluu activated carbon from  oil palm shell  gave iodine absorption of  950  mg/g and yield  of 22 percent by using NaOH as an activatar.For solid  stare fermentation ,  pericarp   gave  the  highes   COD degredation    (61  %),  VS  (31. 4 %),  CIN ratio  (35. 7 %) and  cellulose (26  %) the highest  biogas produation  (0. 211  t/g  COD)  while  bagasse  gave  the highest  lignin degradation  (2. 2  %).For  liquid  state fermentation, The use  of  PUR  as captive  material  gave  the highest   COD,  SS  and  VSS  degradation  either  for  mud waste and waste water.  The highest  COD degradation of mud  waste was 79%, SS 78%,  VSS 79% and biogas production  of  3.7 l/g COD.